2023
DOI: 10.3390/molecules28041885
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Tamarind Shell Extract against Oxidative Stress In Vivo and In Vitro

Abstract: Tamarind shell is rich in flavonoids and exhibits good biological activities. In this study, we aimed to analyze the chemical composition of tamarind shell extract (TSE), and to investigate antioxidant capacity of TSE in vitro and in vivo. The tamarind shells were extracted with 95% ethanol refluxing extraction, and chemical constituents were determined by ultra-performance chromatography–electrospray tandem mass spectrometry (UPLC-MS/MS). The free radical scavenging activity of TSE in vitro was evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The pH value of TSP was ca. 4.5, indicating that TSP was a weak acid due to the abundance of polyphenols [ 2 , 9 , 10 , 11 , 25 ]. The elemental analysis revealed that TSP consisted of approximately 48.0%, 45.6%, 5.7%, and 0.7% of carbon (C), oxygen (O), hydrogen (H), and nitrogen (N), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The pH value of TSP was ca. 4.5, indicating that TSP was a weak acid due to the abundance of polyphenols [ 2 , 9 , 10 , 11 , 25 ]. The elemental analysis revealed that TSP consisted of approximately 48.0%, 45.6%, 5.7%, and 0.7% of carbon (C), oxygen (O), hydrogen (H), and nitrogen (N), respectively.…”
Section: Resultsmentioning
confidence: 99%